Soldiers of diplomacy : the United Nations, peacekeeping, and the new world order - Coulon, Jocelyn (University of Toronto Press, 1998)
"Jocelyn Coulon draws on his experiences visiting nine peacekeeping missions, including those in Cambodia, Bosnia, and Somalia, at a pivotal point in UN history, when UN troops were increasingly acting as warriors of a new world order. He raises important questions: How can the UN distinguish its objectives from the interests of the great powers? Could - and should - the UN maintain an independent army? How can the pitfalls encountered by the peacekeepers in Somalia and Bosnia be avoided? Finally, Coulon urges a return to the original, though less spectacular, role of the UN soldiers: keeping the peace where peace is really the goal of the parties involved."--Jacket